Interpersonal Metadiscourse Markers as Persuasive Function in Joe Biden’s Speech Remarks on Bidenomics 2023 - Andina Silvi Amalia; Rina Sari (Universitas Sanata Dharma, 2025)
This research aimed at finding the interpersonal metadiscourse markers in Joe Biden’s speech remarks on Bidenomics 2023. The researchers also attempted to comprehend in depth the context of interpersonal metadiscourse markers through discourse analysis by analyzing how a speaker used language to interact with the audiences, managing social relationship, and conveying meaning, therefore it used qualitative method. Dafouz’s (2008) theory was used to find the types of interpersonal metadiscourse markers, including Hedges, Certainty markers, Attributors, Attitude markers, and Commentaries. While Mai (2016) theory was also used to classify the types of interpersonal metadiscourse markers into the types of persuasive function in metadiscourse including Logos, Ethos, and Pathos. The researchers discovered 45 data of interpersonal metadiscourse in Joe Biden’s speech, including 4 hedges, 3 certainty markers, 8 attributors, 7 attitude markers, and 23 commentaries. This research also found that 45 interpersonal metadiscourse markers were categorized as persuasive function including 29 markers as ethos, and 27 markers as pathos. However, the types of persuasive function were totally 56 markers because self-mention in ethos, and engagement markers in pathos have the same representative of interpersonal metadiscourse markers which were taken from the type of commentaries. Overall, commentaries were the most frequent markers used by Joe Biden in his speech, while certainty markers were the most infrequent markers used by Joe Biden. Policy speech delivered by Joe Biden affected on how persuasive function was shaped.